Islam and the economic development of Southeast Asia : the islamic voluntary sector in Southeast Asia - Ariff, Mohamed, editor (Singapore : Institute of Southeast Asian Studies (ISEAS), 1991)
Cover title: The Islamic Voluntary Sector in Southeast Asia
Keywords: Charitable uses, trusts and foundations (Islamic law) -- Asia, Southeastern; Economic development -- Religious aspects -- Islam -- Asia, Southeastern; Land trusts (Islamic law) -- Asia, Southeastern ; Zakat